(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Radiation- Induced Oral Mucositis (RIOM) is a frequent debilitating side effect in patients with Head and Neck Cancer (HNC) received Radiotherapy (RT). Objectives: to evaluate and compare between the efficacy of High Level LASER Therapy (HLLT) and Low Level LASER Therapy (LLLT) in treatment of RIOM in patients with HNC. Methods: Sixty patients of both genders with RIOM were enrolled in the study and distributed randomly into 3 groups: Study group (A): 20 patients (8 male and 12 females) were received HLLT by Gallium Arsenide (GA-AS) laser class IV (wavelength 904 nm, average power 3.3W, frequency 1-2000 Hz and energy density 6.04 J/cm2). Scanning mode was used extraorally all over the oral cavity in one minute for five consecutive days, once a day for 2 weeks. Study group (B): 20 patients (6 male and 14 females) were received LLLT GA-AS laser class 3B with a small hand held probe intraorally both in ulcerated and erythematous areas (wavelength 904 nm, average power 70.5mW and energy density 5 J/cm2 for one minute on each point) for five consecutive days, once a day for 2 weeks. Control group (C): 20 patients (9 males and 11 females) were received shame LASER. All patients in the 3 groups were received routine medical care in the form of local antifungal, analgesics and mouth wash. Outcome measures: Patients were evaluated for OM severity according to World Health Organization (WHO) grading scale. Pain intensity was assessed by visual analogue scale (VAS). Assessment of the dependent variables was performed at two occasions: first at baseline, second after two weeks (ten LASER sessions). Results: Within group analysis, there were statistically significant difference between pre and post treatment at all variables in both study groups A and B in favor to group A (p<0.05) but there were no statistical significant difference at control group (C) variables. Between groups analysis at post-treatment revealed that there were statistical significant difference in all measured variables between three group as p<0.05. Conclusion: HLLT has a superior effect in reduction of pain and severity of RIOM compared to LLLT in patients with RIOM.